A method for preparing a solid base catalyst and its application
By loading aluminum salt on the support and combining with sodium hydroxide/potassium hydroxide, the specific surface area and alkalinity of the solid base catalyst are improved, and the problem of low catalyst utilization efficiency in the DMBA preparation process in the prior art is solved, and DMBA preparation with high efficiency and low by-products is achieved.
Patent Information
- Application Number
- CN202411892657.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, sodium hydroxide is not efficient in the preparation of α,α-dimethylbenzyl alcohol (DMBA) in hydrogen peroxide, and common solid base catalysts cannot take into account both the specific surface area and strong alkalinity.
By supporting the aluminum salt on a support with a high specific surface area, combining sodium hydroxide/potassium hydroxide with aluminum oxide, the alkalinity of the solid alkali catalyst is improved, and the bonding between the aluminum salt and the support is enhanced by sonication, thereby improving the specific surface area and alkalinity of the catalyst.
It has achieved efficient preparation of DMBA, with CHP conversion rate reaching more than 95%, and the selectivity of DMBA has also reached more than 95%, with low selectivity of by-products, easy to recover catalysts, and simple process.
Smart Images

Figure BDA0005201006130000101 
Figure BDA0005201006130000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical organic synthesis, and in particular to a preparation method of a solid base catalyst and application thereof. Background Art
[0002] α,α-Dimethylbenzyl alcohol (DMBA) is a white prismatic crystal with a rose scent. It can be used as a fragrance, cosmetics, and flavor preparation. It is also an important organic intermediate and is mainly used in the preparation of dicumyl peroxide (DCP) by reacting with cumene hydroperoxide (CHP). At present, DMBA is prepared using CHP as a raw material. There are four main methods: (1) using water-soluble sulfides and other inorganic reducing agents to reduce CHP, such as sodium sulfide and sodium sulfite. However, this method uses an equivalent amount of inorganic salt and peroxide to react, generating a large amount of wastewater and cheap inorganic acid salts, causing serious environmental pollution. This method is a backward process that is on the way out. (2) Catalytic hydrogenation. CN102040482 discloses a method for preparing α,α-dimethylbenzyl alcohol by hydrogenating cumene hydroperoxide, which mainly solves the problem of poor stability of Pd catalyst in the existing technology of preparing α,α-dimethylbenzyl alcohol by hydrogenating cumene hydroperoxide. This invention introduces alkali metals and alkaline earth metals, and the CHP conversion rate is greater than 99%, and the DMBA selectivity is greater than 99%. However, highly active oxidants and reductants exist in the system at the same time, and the hydrogenation reduction of organic peroxides is a highly exothermic reaction. Therefore, this method has a high risk when applied to large-scale production, and the utilization rate of atomic oxygen is low. (3) Homogeneous catalytic decomposition method. Variable-valence metal ions are used as catalysts, but are limited by the selection of solvents, catalyst recovery, environmental issues, and the decomposition process always produces a considerable amount of by-products such as aromatic aldehydes and ketones in addition to DMBA. (4) Preparation by decomposing CHP under a strong base catalyst. In an alkaline environment, the decomposition product of CHP is mainly dimethylbenzyl alcohol, and the oxygen atoms released by the reaction can oxidize isopropylbenzene, resulting in the production of more dimethylbenzyl alcohol. At present, dimethylbenzyl alcohol is mostly prepared by reacting sodium hydroxide with cumene hydroperoxide. However, a large amount of sodium hydroxide is required in this process. The decomposition product of CHP catalyzed by high-concentration sodium hydroxide is mainly DMBA. However, when the alkali concentration is reduced during the reaction, a large amount of byproduct acetophenone will be produced. In addition, the oxidation liquid is in short-term contact with the aqueous solution, and the alkali utilization efficiency is not high. At the same time, NaOH is difficult to recover, resulting in a complicated product separation process.
[0003] For the fourth strong base catalytic preparation method, in order to solve the problem of the difficulty in separating the strong base catalyst sodium hydroxide, a heterogeneous catalyst can generally be used as a substitute, but the catalytic effect of the alkaline catalyst prepared by current technology is not good. The main reason is that it is difficult to take into account both the specific surface area and the strong alkalinity of the catalyst. For example, in the study of "KOH-Al2O3 solid base catalytic ester exchange synthesis biodiesel" by Li Lin et al., it was found that 20% KOH was loaded on a surface area of 137.6m 2 / g of Al2O3, the specific surface area was significantly reduced to 80.52m 2 / g. However, the surface of hydrated talc catalysts with large specific surface area has both acid and alkali active sites, and it is difficult to obtain strong alkaline sites. Patent CN 117583018 A discloses a production process for a solid base catalyst for preparing propylene glycol, that is, the modified magnesium aluminum hydrotalcite powder is calcined with zeolite powder, glass powder and a binder to form a catalyst precursor, and then modified again with alkaline solution before use, which ensures that the catalyst has good strength and will not be easily lost, and has a high specific surface area, but its alkaline strength is mainly provided by the alkali metal oxide MgO, resulting in low alkalinity of the catalyst.
[0004] Therefore, in order to improve the process efficiency of preparing DMBA by base-catalyzed decomposition and simplify the product separation process, it is urgent to develop solid base catalysts that are easy to recover, have strong alkalinity and large specific surface area. Summary of the invention
[0005] In order to solve the technical problems that the utilization efficiency of sodium hydroxide in the process of preparing DMBA from CHP is low and the commonly used solid base cannot take into account both specific surface area and strong alkalinity, the present invention provides a method for preparing a solid base catalyst, wherein an aluminum salt is first loaded on a carrier with a high specific surface area to obtain a carrier with low alkalinity and a high specific surface area, and then sodium hydroxide / potassium hydroxide is combined with aluminum oxide to improve the alkalinity of the solid base.
[0006] The preparation method of the solid base catalyst comprises the following steps:
[0007] S1) adding a surfactant to an aluminum salt solution and mixing, then adding a carrier and mixing to obtain an aluminum salt-carrier mixed solution, adding ammonia water to the aluminum salt-carrier mixed solution, and allowing to stand for precipitation to obtain a precipitate;
[0008] S2) washing, filtering, drying and calcining the precipitate obtained in step S1) to obtain an alumina modified carrier;
[0009] S3) The alumina modified support obtained in step S2) is immersed in an alkaline solution, and a solid base catalyst is obtained after drying and calcining.
[0010] As a preferred embodiment of the present invention, ultrasonic stirring is performed while adding the carrier to obtain an aluminum salt-carrier mixed solution, ultrasonic stirring is maintained and ammonia water is added, and ultrasonic stirring is continued for 2 to 4 hours after the ammonia water is added, and then the mixture is allowed to stand for precipitation, wherein the ultrasonic frequency is 30 to 50 KHZ. By adding the ultrasonic treatment step, the conversion rate of CHP can be further improved and strong alkalinity can be achieved; the bonding is made stronger, and aluminum oxide can be more evenly loaded on the carrier. The role of loaded aluminum is to prevent alkali from corroding the carrier, and aluminum combines with NaOH / KOH to enhance alkalinity. The prior art has disclosed a method for precipitating loaded aluminum oxide, but the technical effect is not as good as that of the present application, such as low CHP conversion rate and low selectivity.
[0011] The amount of the surfactant used in step S1) accounts for 0.5% to 10% of the total mass of the aluminum salt-carrier mixed solution; the surfactant is used as a dispersant to enhance the bonding effect between the carrier and aluminum, promote the dissolution and dispersion uniformity of the aluminum salt, and further improve the dispersion uniformity of the base when the base is combined, thereby making the strong alkalinity evenly distributed on the surface of the solid base, so as to achieve lower selectivity for the by-product acetophenone.
[0012] The surfactant is selected from one of polyethylene glycol-400, Triton-X100, polyoxyethylene oleate, C8-C10 olefin phenol polyoxyethylene ether, alkylphenol polyoxyethylene ether phosphate or sodium dodecylbenzene sulfonate. The above dispersant is more suitable for the reaction material system of the technical solution of the present invention, which is conducive to controlling the agglomeration and growth of nano powder.
[0013] In step S1), the carrier is a molecular sieve or activated carbon, and its specific surface area is 500-1000m 2 / g, and a large specific surface area is conducive to full contact during the reaction process, thereby improving the decomposition efficiency of CHP; the aluminum salt solution is selected from one of aluminum nitrate solution, aluminum chloride solution, aluminum sulfate solution, aluminum silicate solution or alum, wherein the solid-liquid mass ratio of the carrier to the aluminum salt solution is 1: (10-120); the molar ratio of ammonia to aluminum salt in the ammonia water is 1: (10-20).
[0014] As a preferred embodiment of the present invention, the molecular sieve is sodium zeolite. The sodium zeolite can further improve the effect of aluminum loading, make the bonding between the carrier and aluminum more stable, further improve the service life and stability of the catalyst, and give full play to the synergistic effect of alkali and aluminum, increase the basicity of the catalyst, and further improve the selectivity of DMBA to more than 95. When the silicon-aluminum ratio is greater than 5, the alkaline substance may react with the silicon therein to cause the collapse of the molecular sieve framework. The silicon component in the zeolite is easy to react with KOH / NaOH to generate low-strength alkaline compounds, but KOH / NaOH may react with the aluminum component in the zeolite to generate high-strength alkaline species in local areas, and the influence of the electrostatic field in the zeolite pores enhances the alkalinity. Therefore, the present invention uses sodium zeolite with a silicon-aluminum ratio of (1.5-4.5):1 as a carrier.
[0015] In the step S2), the drying temperature is 40-60° C., and the drying time is 1-2 hours; the calcination temperature is 700-1000° C., and the calcination time is 1-3 hours.
[0016] In order to improve the alkalinity strength, the alkaline solution in step S3) is a NaOH solution and / or a KOH solution. Although a higher catalytic effect can be obtained when the amount of NaOH / KOH loaded is small, when the NaOH / KOH loading is too high, the alumina carrier is close to saturation, and further increase will only form a multi-layer dispersion, which is not conducive to the full play of the catalytic activity. Therefore, the amount of alkali used is best 10% to 50% of the carrier mass.
[0017] In the step S3), the immersion time is 12 to 24 hours; the drying temperature is 100 to 150° C., and the drying time is 6 to 12 hours; the roasting temperature is 400 to 600° C., and the roasting time is 4 to 6 hours.
[0018] Another object of the present invention is to provide the use of the solid base catalyst prepared by the above preparation method in the preparation of α, α-dimethylbenzyl alcohol.
[0019] The third object of the present invention is to provide a method for preparing α,α-dimethylbenzyl alcohol, wherein the preparation method uses cumene hydroperoxide solution as a raw material, and decomposes cumene hydroperoxide under the action of a solid base catalyst prepared by the above preparation method to prepare α,α-dimethylbenzyl alcohol. The solid base catalyst prepared by the present invention is used to prepare α,α-dimethylbenzyl alcohol, with low by-products, high yield of DMBA, easy separation of the catalyst, and simple process.
[0020] The mass concentration of the cumene hydroperoxide solution is 5-50wt%, and the amount of the solid base catalyst is 1%-10% of the mass of the cumene hydroperoxide; the oxygen content during decomposition of the cumene hydroperoxide is lower than 20%, and the decomposition time is 4-12h.
[0021] Beneficial effects of the present invention:
[0022] (1) Adding an ultrasonic treatment step makes the bonding stronger, and aluminum oxide can be evenly loaded on the carrier. The role of loaded aluminum is to prevent alkali from corroding the carrier, and aluminum oxide combines with NaOH / KOH to enhance alkalinity. At the same time, a surfactant is used as a dispersant to promote the dissolution and uniformity of the aluminum salt, thereby improving the uniformity of the dispersion of the base when the base is combined, and then making the strong alkalinity evenly distributed on the surface of the solid base to achieve a lower selectivity for the by-product acetophenone.
[0023] (2) The solid base catalyst prepared by the present invention has a large specific surface area and strong alkalinity, which can improve the reaction efficiency. The CHP conversion efficiency is more than 95%, the DMBA selectivity is more than 95%, and the selectivity of the by-products acetophenone and phenol is low and easy to recover. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.
[0025] The characterization method used in the present invention is: using a fully automatic physical and chemical adsorption instrument Quantachrome Autosorb-1-C-MS to measure the specific surface area of the catalyst; using liquid chromatography to detect the organic component.
[0026] The reagents used in the present invention are all commercially available products.
[0027] Example 1
[0028] Dissolve 12.8g aluminum nitrate in 600ml deionized water to prepare a 0.1mol / L aluminum salt solution, then add 4.8g of polyethylene glycol-400 as a dispersant. Dissolve 10g of NaY zeolite (silicon-aluminum molar ratio of 1.5-4.5:1, specific surface area of 781m 2 / g) was added to the aluminum nitrate solution, and ultrasonic stirring was performed at a frequency of 40KHZ to obtain an aluminum salt-NaY mixed solution. 60g of 25% ammonia water was added dropwise as a precipitant to the aluminum salt-NaY mixed solution under ultrasonic stirring. After the addition of ammonia water was completed, ultrasonic stirring was continued for 3 hours and then allowed to stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. The obtained white colloidal precipitate was filtered, washed with deionized water for more than three times, dried at 50°C for 1 hour, and calcined at 800°C for 2 hours to obtain 12.8g of Al2O3-NaY powder. Weigh 2.6 g of NaOH and put it in a beaker. Add 12.8 mL of deionized water to make a solution. Then put 12.8 g of Al2O3-NaY powder in the solution, soak it at room temperature for 12 h, dry it in a 120 ° C oven for 8 h, and calcine it in a 500 ° C muffle furnace for 6 h to obtain 15.4 g of NaOH-Al2O3-NaY zeolite catalyst. The peak area of 631 m2 / g.
[0029] Weigh 1.50g of the above catalyst and 50g of 30% CHP and add them into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6h under normal pressure. The oxygen content of the exhaust gas during the reaction is about 10%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0030] Example 2
[0031] Dissolve 25.6g aluminum nitrate (300ml) in deionized water to prepare a 0.4mol / L aluminum salt solution, then add 24g of polyethylene glycol-400 as a dispersant. Dissolve 15g of NaY zeolite (silicon-aluminum molar ratio of 1.5-4.5:1, specific surface area of 815m 2 / g) was added to the aluminum nitrate solution, and ultrasonic stirring was performed at a frequency of 40KHZ to obtain an aluminum salt-NaY mixed solution. 84g of 25% ammonia water was added dropwise as a precipitant to the aluminum salt-NaY mixed solution under ultrasonic stirring. After the addition of ammonia water was completed, ultrasonic stirring was continued for 3 hours and then allowed to stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. The obtained white colloidal precipitate was filtered, washed with deionized water for more than three times, dried at 50°C for 1 hour, and calcined at 900°C for 2 hours to obtain 21.0g of Al2O3-NaY powder. Weigh 6.3g NaOH into a beaker, add 21mL deionized water to make a solution, then weigh 21.0g Al2O3-NaY powder into the solution, soak at room temperature for 12h, dry in a 120℃ oven for 8h, and calcine in a 500℃ muffle furnace for 6h to obtain 27.3g NaOH-Al2O3-NaY zeolite catalyst. The peak area is 618m 2 / g.
[0032] Weigh 2.50g of the above catalyst and 50g of 30% CHP into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6h at normal pressure. The oxygen content of the exhaust gas during the reaction is about 10%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0033] Example 3
[0034] The NaOH-Al2O3-NaY zeolite catalyst was prepared by the same method as in Example 1. No ultrasound was performed during the preparation process. 14.3 g of catalyst was obtained. The specific surface area of the catalyst was 687 m 2 / g.
[0035] Weigh 1.50g of the above catalyst and 50g of 30% CHP and add them into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6h under normal pressure. The oxygen content of the exhaust gas during the reaction is about 10%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0036] Example 4
[0037] Dissolve 42.6g aluminum nitrate (1000ml) in deionized water to prepare a 0.2mol / L aluminum salt solution, then add 40g of polyethylene glycol-400 as a dispersant. Dissolve 10g of NaY zeolite (silicon-aluminum molar ratio of 1.5-4.5:1, specific surface area of 815m 2 / g) was added to the aluminum nitrate solution, and ultrasonic stirring was performed at a frequency of 40KHZ to obtain an aluminum salt-NaY mixed solution. 200g of 25% ammonia water was added dropwise as a precipitant to the aluminum salt-NaY mixed solution under ultrasonic stirring. After the addition of ammonia water was completed, ultrasonic stirring was continued for 4 hours and then allowed to stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. The obtained white colloidal precipitate was filtered, washed with deionized water for more than three times, dried at 40°C for 2 hours, and calcined at 900°C for 2 hours to obtain 20.2g of Al2O3-NaY powder. Weigh 2.02g KOH into a beaker, add 20mL deionized water to make a solution, then weigh 20.2g Al2O3-NaY powder into the solution, soak at room temperature for 12h, dry in a 120℃ oven for 8h, and calcine in a 500℃ muffle furnace for 6h to obtain 22.2g KOH-Al2O3-NaY zeolite catalyst. The peak area is 534m 2 / g.
[0038] Weigh 2.50g of the above catalyst and 50g of 30% CHP into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 8h under normal pressure. The oxygen content of the exhaust gas during the reaction is about 11%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0039] Example 5
[0040] Dissolve 42.6g aluminum nitrate (1000ml) in deionized water to prepare a 0.2mol / L aluminum salt solution, then add 40g of polyethylene glycol-400 as a dispersant. Dissolve 10g of NaY zeolite (silicon-aluminum molar ratio of 1.5-4.5:1, specific surface area of 815m 2 / g) was added to the aluminum nitrate solution, and ultrasonic stirring was performed at a frequency of 40KHZ to obtain an aluminum salt-NaY mixed solution. 200g of 25% ammonia water was added dropwise as a precipitant to the aluminum salt-NaY mixed solution under ultrasonic stirring. After the addition of ammonia water was completed, ultrasonic stirring was continued for 4 hours and then allowed to stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. The obtained white colloidal precipitate was filtered, washed with deionized water for more than three times, dried at 40°C for 2 hours, and calcined at 900°C for 2 hours to obtain 20.2g of Al2O3-NaY powder. Weigh 10.1g KOH into a beaker, add 20mL deionized water to make a solution, then weigh 20.2g Al2O3-NaY powder into the solution, soak at room temperature for 12h, dry in a 120℃ oven for 8h, and calcine in a 500℃ muffle furnace for 6h to obtain 30.2g KOH-Al2O3-NaY zeolite catalyst. The peak area is 511m 2 / g.
[0041] Weigh 1.0 g of the above catalyst and 50 g of 45% CHP and add them into a 250 ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1 L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6 hours under normal pressure. The oxygen content of the exhaust gas during the reaction is about 11%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0042] Example 6
[0043] Dissolve 42.6g of aluminum nitrate (500ml) in deionized water to prepare a 0.4mol / L aluminum salt solution, then add 12.5g of oleic acid polyoxyethylene dispersant. Dissolve 10g of NaY zeolite (silicon-aluminum molar ratio of 1.5-4.5:1, specific surface area of 815m 2 / g) was added to the aluminum nitrate solution, and ultrasonic stirring was performed at a frequency of 30KHZ to obtain an aluminum salt-NaY mixed solution. 200g of 25% ammonia water was added dropwise as a precipitant to the aluminum salt-NaY mixed solution under ultrasonic stirring. After the addition of ammonia water was completed, ultrasonic stirring was continued for 4 hours and then allowed to stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. The obtained white colloidal precipitate was filtered, washed with deionized water for more than three times, dried at 40°C for 2 hours, and calcined at 800°C for 3 hours to obtain 18.7g of Al2O3-NaY powder. Weigh 6.3g KOH into a beaker, add 20mL deionized water to make a solution, then weigh 18.7g Al2O3-NaY powder into the solution, soak at room temperature for 18h, dry in a 150℃ oven for 6h, and calcine in a 400℃ muffle furnace for 6h to obtain 25.0g KOH-Al2O3-NaY zeolite catalyst. The peak area is 578m 2 / g.
[0044] Weigh 1.0 g of the above catalyst and 50 g of 45% CHP and add them into a 250 ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1 L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6 hours under normal pressure. The oxygen content of the exhaust gas during the reaction is about 10%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0045] Example 7
[0046] Dissolve 8.0g aluminum chloride in 300ml deionized water to prepare a 0.2mol / L aluminum salt solution, then add 12g of polyethylene glycol-400 as a dispersant. Dissolve 10g of NaY zeolite (silicon-aluminum molar ratio of 1.5-4.5:1, specific surface area of 781m 2 / g) was added to the above aluminum chloride solution and ultrasonically stirred at a frequency of 40KHZ to obtain an aluminum salt-NaY mixed solution. 60g of 25% ammonia water was added dropwise as a precipitant to the aluminum salt-NaY mixed solution under ultrasonic stirring. After the addition of ammonia water was completed, ultrasonic stirring was continued for 2 hours and then allowed to stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. The obtained white colloidal precipitate was filtered, washed with deionized water for more than three times, dried at 50°C for 1 hour, and calcined at 800°C for 2 hours to obtain 12.9g of Al2O3-NaY powder. Weigh 2.6g NaOH into a beaker, add 12.9mL deionized water to make a solution, then put 12.9g Al2O3-NaY powder into the solution, soak at room temperature for 12h, dry in a 120℃ oven for 8h, and calcine in a 500℃ muffle furnace for 6h to obtain 15.5g NaOH-Al2O3-NaY zeolite catalyst. The peak area is 637m 2 / g.
[0047] Weigh 1.50g of the above catalyst and 50g of 30% CHP and add them into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6h under normal pressure. The oxygen content of the exhaust gas during the reaction is about 10%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0048] Example 8
[0049] Dissolve 9.6g of aluminum sulfate in 200ml of deionized water to prepare a 0.14mol / L aluminum salt solution, then add 12g of sodium dodecylbenzene sulfonate as a dispersant. 2 / g) was added to the aluminum sulfate solution and ultrasonically stirred at a frequency of 50KHZ to obtain an aluminum salt-activated carbon mixture. 20g of 25% ammonia water was added dropwise as a precipitant to the aluminum salt-activated carbon mixture under ultrasonic stirring. After the addition of ammonia water was completed, ultrasonic stirring was continued for 2 hours and then allowed to stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. The obtained white colloidal precipitate was filtered, washed with deionized water for more than three times, dried at 40°C for 1.5 hours, and calcined at 700°C for 3 hours to obtain 22.5g of Al2O3-activated carbon powder. Weigh 2.3g NaOH into a beaker, add 25mL deionized water to make a solution, then put 22.5g Al2O3-activated carbon powder into the solution, soak at room temperature for 24h, dry in a 100℃ oven for 12h, and calcine in a 600℃ muffle furnace for 4h to obtain 24.8g NaOH-Al2O3-activated carbon catalyst. The peak area is 654m 2 / g.
[0050] Weigh 5.0 g of the above catalyst and 50 g of 5% CHP and add them into a 250 ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1 L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 12 hours under normal pressure. The oxygen content of the exhaust gas during the reaction is about 5%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0051] Comparative Example 1
[0052] Weigh 1.50g NaOH and 50g 30% CHP and add them into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6h under normal pressure. The oxygen content of the exhaust gas during the reaction is about 9%. After the reaction, filter and separate, and analyze the components of the reaction liquid.
[0053] Comparative Example 2
[0054] Weigh 2.6 g of NaOH into a beaker, add 10 mL of deionized water to make a solution, take 10 g of NaY powder (specific surface area 781 m 2 / g) was placed in the solution, immersed at room temperature for 12 hours, placed in a 120℃ oven for 8 hours, and calcined in a 500℃ muffle furnace for 6 hours to obtain 12.6g of NaOH-NaY zeolite catalyst. The peak area was 623m 2 / g.
[0055] Weigh 1.50g of the above catalyst and 50g of 30% CHP into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring paddle speed is 200 rpm, and the reaction is continued for 6h under normal pressure. The oxygen content of the exhaust gas during the reaction is about 8%. After the reaction is completed, the reaction liquid is filtered and separated, and the components of the reaction liquid are analyzed.
[0056] Comparative Example 3
[0057] Dissolve 12.8g aluminum nitrate in 600ml deionized water to prepare 0.1mol / L aluminum salt solution, then add 0.02mol / L polyethylene glycol-400 as a dispersant, and ultrasonically stir at 40KHZ frequency to obtain aluminum salt solution. Add 60g 25% ammonia water as a precipitant dropwise to the aluminum salt-NaY mixed solution under ultrasonic stirring. After the addition of ammonia water, continue ultrasonic stirring for 3 hours and then stand for 2 days to obtain a white colloidal precipitate Al(OH)3·nH2O. Filter the obtained white colloidal precipitate, wash with deionized water for more than three times, dry at 50℃ for 1h, and calcine at 800℃ for 2h to obtain 2.8g Al2O3 powder. Weigh 2.6g NaOH into a beaker, add 2.8mL deionized water to make a solution, then put 2.8g Al2O3 powder into the solution, soak at room temperature for 12h, dry in a 120℃ oven for 8h, and calcine in a 500℃ muffle furnace for 6h to obtain 5.4g NaOH-Al2O3 catalyst. The peak area is 43m 2 / g.
[0058] 1.50 g of the above catalyst and 50 g of 30% CHP were weighed and added into a 250 ml reactor with condensation reflux. The reaction temperature was 55°C, the nitrogen flow rate was 0.1 L / min, the stirring paddle speed was 200 rpm, and the reaction was continued for 6 h at normal pressure. The oxygen content of the exhaust gas during the reaction was about 9%. After the reaction was completed, the reaction liquid was filtered and separated, and the components of the reaction liquid were analyzed.
[0059] Comparative Example 4
[0060] The 20.8% KNO3-18% Al2O3-NaY zeolite catalyst was prepared by the method provided in "Preparation of Al2O3-NaY New Composite Porous Catalytic Material by Alcohol Salt Hydrolysis". The specific surface area was 584m 2 / g.
[0061] Then, 1.50 g of the above catalyst and 50 g of 30% CHP were weighed and added into a 250 ml reactor with condensation reflux. The reaction temperature was 55°C, the nitrogen flow rate was 0.1 L / min, the stirring paddle speed was 200 rpm, and the reaction was continued for 6 hours under normal pressure. During the reaction, the oxygen content of the exhaust gas was about 9%. After the reaction was completed, the reaction liquid was filtered and separated, and the components of the reaction liquid were analyzed.
[0062] Comparative Example 5
[0063] The NaOH-Al2O3-NaY zeolite catalyst was prepared by the same method as in Example 1, wherein the silicon-aluminum molar ratio of the NaY zeolite was 5-8:1, and 15.4 g of catalyst was obtained. The specific surface area of the catalyst was 521 m 2 / g. Weigh 1.50g of the above catalyst and 50g of 30% CHP and add them into a 250ml reactor with condensation reflux. The reaction temperature is 55°C, the nitrogen flow rate is 0.1L / min, the stirring blade speed is 200 rpm, and the reaction is continued for 6h under normal pressure. The oxygen content of the exhaust gas during the reaction is about 8%. After the reaction is completed, it is filtered and separated, and the components of the reaction liquid are analyzed.
[0064] Table 1 Evaluation table of catalytic effect of solid base catalyst
[0065]
[0066]
[0067] The experimental data of the present invention also mainly revolves around the technical characteristics, which mainly reflect that the solid base catalyst with large specific surface area and strong alkalinity has good CHP conversion rate and DMBA selectivity; while in the comparative example, under the same catalyst dosage, the catalyst with weak alkalinity and large specific surface area (such as the comparative example without aluminum loading) has low DMBA selectivity, and the catalyst with strong alkalinity and small specific surface area (such as the comparative example NaOH-Al2O3) has a long reaction time, and the conversion rate and selectivity are not high enough).
[0068] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the specific implementation mode of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A method for preparing a solid base catalyst, characterized in that: The preparation method comprises the following steps: S1) adding a surfactant to an aluminum salt solution and mixing, then adding a carrier and mixing to obtain an aluminum salt-carrier mixed solution, adding ammonia water to the aluminum salt-carrier mixed solution and stirring, and allowing to stand and precipitate to obtain a precipitate; S2) washing, filtering, drying and calcining the precipitate obtained in step S1) to obtain an alumina modified carrier; S3) The alumina modified support obtained in step S2) is immersed in an alkaline solution, and a solid base catalyst is obtained after drying and calcining.
2. The preparation method according to claim 1, characterized in that: In step S1), while adding the carrier, ultrasonic stirring is performed to obtain an aluminum salt-carrier mixed solution, and ultrasonic stirring is maintained and ammonia water is added. After the addition of ammonia water is completed, ultrasonic stirring is continued for 2 to 4 hours and then allowed to settle, wherein the ultrasonic frequency is 30 to 50 KHZ.
3. The preparation method according to claim 1, characterized in that: The amount of the surfactant used in step S1) accounts for 0.5% to 10% of the total mass of the aluminum salt-carrier mixed solution; the surfactant is selected from one of polyethylene glycol-400, Triton-X100, polyoxyethylene oleate, C8-C10 olefin phenol polyoxyethylene ether, alkylphenol polyoxyethylene ether phosphate or sodium dodecylbenzene sulfonate.
4. The preparation method according to claim 1, characterized in that: In step S1), the carrier is a molecular sieve or activated carbon, and its specific surface area is 500 to 1000 m 2 / g; the aluminum salt solution is selected from one of aluminum nitrate solution, aluminum chloride solution, aluminum sulfate solution, aluminum silicate solution or alum, wherein the solid-liquid mass ratio of the carrier to the aluminum salt solution is 1:(10-120); the molar ratio of ammonia to aluminum salt in the ammonia water is 1:(10-20).
5. The preparation method according to claim 4, characterized in that: The molecular sieve is sodium zeolite, wherein the silicon-aluminum molar ratio of the sodium zeolite is (1.5-4.5):
1.
6. The preparation method according to claim 1, characterized in that: In the step S2), the drying temperature is 40-60° C., and the drying time is 1-2 hours; the calcination temperature is 700-1000° C., and the calcination time is 1-3 hours.
7. The preparation method according to claim 1, characterized in that: In the step S3), the alkaline solution is a NaOH solution and / or a KOH solution, wherein the amount of the alkali is 10% to 50% of the mass of the alumina modified support; the impregnation time is 12 to 24 hours; the drying temperature is 100 to 150° C., and the drying time is 6 to 12 hours; the calcination temperature is 400 to 600° C., and the calcination time is 4 to 6 hours.
8. Use of the solid base catalyst prepared by the preparation method according to any one of claims 1 to 7 in the preparation of α,α-dimethylbenzyl alcohol.
9. A method for preparing α,α-dimethylbenzyl alcohol, characterized in that: Using cumene hydroperoxide solution as a raw material, cumene hydroperoxide is decomposed under the action of a solid base catalyst prepared by the preparation method according to any one of claims 1 to 7 to prepare α,α-dimethylbenzyl alcohol.
10. The preparation method according to claim 9, characterized in that: The mass concentration of the cumene hydroperoxide solution is 5-50wt%, and the amount of the solid base catalyst is 1%-10% of the mass of the cumene hydroperoxide; the oxygen content during decomposition of the cumene hydroperoxide is lower than 20%, and the decomposition time is 4-12h.
Citation Information
Patent Citations
Production process of solid base catalyst for preparing propylene glycol
CN117583018A